2020
DOI: 10.5713/ab.20.0355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of β-mannanase on growth performance, carcass characteristics, excreta microflora, blood constituents, and nutrient ileal digestibility in broiler chickens

Abstract: Objective: The aim of the present study was to investigate the effects of dietary supplementation of β-mannanase on growth performance, carcass characteristics, excreta microflora, blood constituents, and nutrient digestibility in broiler chickens. Methods: A total of 680 one-d-old Ross 308 (as hatched) broiler chickens were used in a 35-d growth assay. Chicks were sorted into pens with 17 birds/pen and 10 pens/treatment. Treatment diets were contained either 44% or 48% crude protein (CP) soybean meal (SBM) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Agboola et al (2013) showed no significant effect of dietary enzyme supplementation on carcass and liver weight but reduced gizzard size of broilers. Some researchers reported that adding enzymes to diets did not affect relative weight of liver and gizzard of broiler chickens (Hassanein 2011;Emadinia et al 2014;Mohammadigheisar et al 2021). The present study also showed that BS4 enzyme supplementation did not significantly influence relative weight of liver and gizzard of broilers.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Agboola et al (2013) showed no significant effect of dietary enzyme supplementation on carcass and liver weight but reduced gizzard size of broilers. Some researchers reported that adding enzymes to diets did not affect relative weight of liver and gizzard of broiler chickens (Hassanein 2011;Emadinia et al 2014;Mohammadigheisar et al 2021). The present study also showed that BS4 enzyme supplementation did not significantly influence relative weight of liver and gizzard of broilers.…”
Section: Discussionsupporting
confidence: 43%
“…The ME: protein ratio imbalances might not occur since the BS4 enzyme improved ME, protein, and amino acids digestibility of the feed (Pasaribu et al 2009;Sinurat et al 2014). Emadinia et al (2014) and Mohammadigheisar et al (2021) also reported similar results.…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, β-mannanase improved AME by 143 kcal/kg concomitant with 3% improvement on growth and FCR. β-Mannanase supplementation has been demonstrated to have positive effects on performance and nutrient digestibility in poultry fed corn-SBM-based diets as well as diets containing guar meal, copra meal, and other β-mannan-containing components ( Daskiran et al, 2004 ; Jackson et al, 2004 ; Ferreira et al, 2016 ; Balasubramanian et al, 2018 ; Caldas et al, 2018 ; Mohammadigheisar et al, 2021 ). Some of these positive effects have been ascribed to mechanisms that are different compared to the modes of action of other NSP carbohydrases such as reducing FIIR.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that β-mannanase might have decreased digesta flow rate due to the greater hydrolysis of copra meal leading to improved nutrient utilization. It has also been demonstrated that β-mannanase improved digestibility of valine, methionine, and leucine in broiler chickens fed corn-SBM diet ( Mohammadigheisar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Abdollahi et al (2022), feed acidification improves the efficacy of exogenous enzymes by lowering the pH of the diet and digesta. There are recent studies on the positive effects of the separate supplementation of citric acid (Abd-Elsamee, 2020) and β-Mannanase (Mohammadigheisar et al, 2021). One unit of mannanase activity was defined as the amount of enzyme which generates 0.72 micrograms of reducing sugars per minute from a mannosecontaining substrate at pH 6.6 and a temperature of 104°F (Caldas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%